Perlindungan Hukum bagi Kreditur dalam Perjanjian Utang-Piutang Berbasis Fintech Lending di Indonesia: Perspektif Hukum Perdata dan Hukum Dagang - Heriyanto Heriyanto (STIKes Ibnu Sina Ajibarang, 2026)
The development of financial technology (fintech lending) in Indonesia has significantly facilitated public access to financing; however, it has also generated various legal issues, particularly concerning the protection of creditors. This study aims to analyze the forms of legal protection available to creditors in loan agreements based on fintech lending from the perspectives of civil law and commercial law in Indonesia. The research employs a normative legal method, utilizing both statutory and conceptual approaches. The findings indicate that legal protection for creditors in fintech lending still faces numerous challenges, particularly regarding the validity of electronic agreements, the risk of default, and the weakness of guarantee mechanisms. Existing regulations, such as the Financial Services Authority Regulation (POJK) concerning information technology-based lending services, have not yet provided optimal legal certainty. Furthermore, the principles of prudence and transparency have not been fully implemented by fintech providers. Therefore, strengthening regulatory frameworks and harmonizing civil law and commercial law are essential to ensure more comprehensive legal protection for creditors. This study is expected to contribute to the development of business law in Indonesia, particularly in responding to the dynamics of the digital economy.